Project R2D2 - Alam, Rakib Hassan Sunny; Al Samir, Abdullah; Sanzid, Syeada; Newaz, Ali (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.